Incidence of Vibrio parahaemolyticus in fisli products marketed in Cochin - Sanjeev, S; Stephen, Jose (Indian Journal of Fisheries, 2011)
Because of world-wide distribution ofVibrio parahaemolyticus in seawater andbrackishwater it is extremely difficult toprevent the occurrence of this organism inraw sea foods (Karunasagar et al. 1984).However, measures to control itsmultiplication in seafood and to preventrecontamination of cooked foods are needed(Liston 1974, Sakazaki et al. 1979).